Pitié pour les Communards ! Victor Hugo face au royaume de Belgique - Brix, Michel (Verbum – Analecta Neolatina, 2012)
Victor Hugo constantly fought for the abolition of the death penalty. One of his earliest works, Le Dernier Jour d’un condamné (1829), was already devoted to this issue. The present paper discusses how Hugo fought against those who insisted on shooting the troublemakers in the wake of the Parisian Commune (1871). These efforts put the writer in danger: he was living in Belgium at the time and was made to leave the country by order of the government. These events shed a particular light on the genesis of the poem called Les Fusillés in the collection of L’Année terrible.